Thomas Langur (Presbytis thomasi) Daily Movement in Jantho Natural Reserve, Aceh Province - Ruskhanidar; Rosmalia; Sofyan Iskandar (Universitas Nusa Bangsa, 2023)
Thomas langur (Presbytis thomasi) is an endemic primate to Aceh and North Sumatra. These primates have a local name, “Kedih.” Forest fires and forest functions conversion into oil palm plantations are pressure on their habitat and have decreased wild populations in nature. As arboreal animals, their movements depend heavily on the connectivity of vegetation. Comprehensive research is needed to obtain horizontal and vertical daily movement data of the thomas langur. This study used GPS to take coordinates, a camera to document Thomas langur and its food trees, and Thomas langur as a research object. The data recorded includes the coordinates of each forage tree, the type of forage tree, and the height of the canopy strata used by Thomas langur for foraging. The hardwood movement data was plotted on ArGis 10.1 to get the horizontal hardness movement area. Tree height data was obtained by measuring the tree height where Thomas langur stopped to look for food. Kedih movements to look for food are carried out daily from morning to evening. The results showed that the short length of movement was highly depend on the availability of forage trees. The denser the forage trees, the shorter the daily activities of Thomas langur. This daily movement can be done horizontally and vertically. Horizontally, Thomas langur moved to follow the forage trees, and vertically, Thomas langur moved by utilizing the height of the forage trees. Horizontally, Thomas langur moved 144.92 m in the rehabilitation block and 62.30 m in the protection block. The Thomas langur home ranged in the rehabilitation block is 27 ha, and 25 ha in the protected block. Vertically, Kedih in the rehabilitation blocks and protected blocks moved to trees with a height of 11-20 m, as much as 49%.